2021
DOI: 10.3390/nu13114104
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status of the British African-Caribbean Residents: Analysis of the UK Biobank Cohort

Abstract: The vitamin D status of the United Kingdom (UK) African-Caribbean (AC) population remains under-researched, despite an increased risk of vitamin D deficiency due to darker skin phenotypes and living at a high latitude. This cross-sectional study explored the vitamin D status and intake of AC individuals (n = 4046 with a valid serum 25(OH)D measurement) from the UK Biobank Cohort, aged ≥40 years at baseline (2006–2010). Over one third of the population were deficient (<25 nmol/L), 41.1% were insufficient (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…In a 2021 investigation of vitamin D status in 4,046 African Caribbean individuals in the UK, logistic regression showed that brown or black skin phenotype, together with blood draw (for serum 25(OH)D measurement) being carried out in winter or autumn and non-use of vitamin D supplements, predicted significantly increased odds of vitamin D deficiency 145 . On the other hand, a large body of evidence, as synthesized in a review analysing 36 studies, has confirmed that African American patients experience more severe SLE and a wider range of adverse outcomes than patients of other racial/ethnic groups 146 .…”
Section: Vitamin D and Interconnections With Autoimmune Rheumatic Dis...mentioning
confidence: 99%
“…In a 2021 investigation of vitamin D status in 4,046 African Caribbean individuals in the UK, logistic regression showed that brown or black skin phenotype, together with blood draw (for serum 25(OH)D measurement) being carried out in winter or autumn and non-use of vitamin D supplements, predicted significantly increased odds of vitamin D deficiency 145 . On the other hand, a large body of evidence, as synthesized in a review analysing 36 studies, has confirmed that African American patients experience more severe SLE and a wider range of adverse outcomes than patients of other racial/ethnic groups 146 .…”
Section: Vitamin D and Interconnections With Autoimmune Rheumatic Dis...mentioning
confidence: 99%
“…76 Currently, vitamin D 1518 deficiency or insufficiency is a major global health issue. [77][78][79][80][81][82][83][84][85][86][87][88] Obese people, people of color, and those individuals who live in high altitudes are more likely to have vitamin D insufficiency or deficiency. [78][79][80]84,89 Additionally, children and pregnant women are particularly vulnerable to have vitamin D deficiency or insufficiency.…”
Section: The Potential Effects Of Vitamin D In the Etiology Behind As...mentioning
confidence: 99%
“…[77][78][79][80][81][82][83][84][85][86][87][88] Obese people, people of color, and those individuals who live in high altitudes are more likely to have vitamin D insufficiency or deficiency. [78][79][80]84,89 Additionally, children and pregnant women are particularly vulnerable to have vitamin D deficiency or insufficiency. 77,90 A multi-center cross-sectional study conducted in England indicated that up to 14% children under the age of seven were vitamin D deficient.…”
Section: The Potential Effects Of Vitamin D In the Etiology Behind As...mentioning
confidence: 99%
“…
Vitamin D status has been found to be inversely associated with risk of respiratory tract infections (RTIs) (1) . It varies by ethnicity, with several ethnic minority groups in the United Kingdom (UK) reported to be at a higher risk of vitamin D deficiency (serum 25-hydroxyvitamin D (25(OH)D) concentrations <25 nmol/L) compared to their white counterparts (2,3) . However, the relationship between serum 25(OH)D concentrations and incidence of RTIs by ethnicity in the UK remains unclear.
…”
mentioning
confidence: 99%